Influence of sol counter-ions on the anatase-to-rutile phase transformation and microstructure of nanocrystalline TiO21. Issue 8 (28th February 2015) - Tobaldi, D. M.; Pullar, R. C.; Gualtieri, A. F.; Belen Jorge, A.; Binions, R.; McMillan, P. F.; Seabra, M. P.; Labrincha, J. A.
<x xml:space="preserve">Abstract</x> Amongst nanomaterials, metal oxides play an increasingly dominant role, with titanium dioxide (titania, TiO2) being widely used for various applications, such as light-to-energy conversion and storage, and photocatalysis.